Multi-Threaded Message Dispatcher - a Design Pattern with Innate Support for Mission Critical Applications - Marcel-Titus Marginean; Chao Lu (International Journal of Networked and Distributed Computing (IJNDC), 2016)
The usage of well-tried software design patterns and application frameworks is often encountered in Mission and Safety Critical Applications development due to the high stakes involved in the case of failures. To increase reliability, some frameworks attempt to separate the implementation of business logic and low level implementation details and move the latter inside of framework-implementation in order to allow the developers to focus on the problem as much as possible, while still providing the necessary infrastructure in easy to use API’s. In this paper we present a framework for message processing which takes advantage of the newer C++11 features to enforce separation of concerns, perform dead-lock avoidance, and encourage unit testing. This paper expands on our previous work presented in June 2016 at IEEE/ACIS SERA.